BEGONIA TANGGAMUSENSIS, A NEW SPECIES OF BEGONIA SECT. PLATYCENTRUM FROM GUNUNG TANGGAMUS, SUMATRA AND NOTES ON ALLIED SPECIES BEGONIA SCOTTII AND BEGONIA PSEUDOSCOTTII - HUGHES, MARK; GIRMANSYAH, DEDEN (REINWARDTIA, 2024)
A new species, Begonia tanggamusensis Girm. & M.Hughes (§ Platycentrum), is described from Gunung Tanggamus in southern Sumatra, where it is endemic. It grows on moss covered rocks and at the base of large trees in montane forests at an elevation of 1,700–2,000 m. A provisional conservation assessment places the species in the Near Threatened category.